Over a million students use our free study notes to help them with their homework
cos(2x) = 2cos2(x) - 1 This is the identity. Therefore we can substitute in 2[cos2(x)] to be 2 multiplied by (1/4)2.Therefore cos(2x) = 2(1/4)(1/4) - 1 = 2/16 - 1 = 2/16 -...
(3x-4)/(x+2)(x-3) = A/(x+2) + B/(x-3)=> 3x-4 = A(x-3) + B(x+2)Let x = -2-10 = -5AA = 2Let x = 35 = 5BB = 1∴ (3x-4)/(x+2)(x-3) = 2/(x+2) + 1/(x-3)
First complete the square for both x and y. Move all constants to the right hand side. The square root of this is the radius of the circle. The two constants in the completed square bracket show the x and...
To simplify the fraction first notice (1-x2) = (1-x)(1+x) so the common factor of (1+x) in the numerator and denominator can be cancelled. (1+x)/((1-x^2)(2x+1)) = 1/((1-x)(2x+1)), then we need ...
Rearrange to (74)2 = ((72)2)272 = 49(72)2 = 492 = (50-1)2 = 502 - 2x50 + 1 = 24017<...
←
113
114
115
116
117
→
Internet Safety
Payment Security
Cyber
Essentials